Force-Controlled Robotic Assembly Processes of Rigid and Flexible Objects Methodologies and Applications - Ghalyan, Ibrahim Fahad Jasim (Springer International Publishing : Imprint: Springer, 2016)
This book provides comprehensive and integrated approaches for rigid and flexible object assembly. It presents comparison studies with the available force-guided robotic processes and covers contact-state modeling, scheme control strategies, and position searching algorithms. Further, it includes experimental validations for different assembly situations, including those for the assembly of industrial parts taken from the automotive industry. .